English Language Teachers’ Professional Training: The Analysis of the Catalogue of Professional Development Programmes for Employees in Education - Kulić, Danijela G.; Kostić Minić, Anđela S. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
A continuing professional development of teachers has always been a necessity in education, but nowadays it is acknowledged as a requirement that has to be fulfilled within the scope of teachers’ lifelong learning, which means that teachers are provided with many formal opportunities to continuously revise and develop their knowledge and skills after graduation. This paper aims to evaluate the presence of teacher training programmes, offered by the Institute for Improvement of Education and Upbringing, that are specifically created for English language teachers and their development in the subject matter (language skills and systems) and English language teaching methodology. According to the results of the research, there are several conclusions that can be drawn: a huge diversity of topics and aims is found in the Catalogue; majority of training programmes are focused on general topics in education (260), upbringing (166), and additional support (49). Seminars that are specifically designed for foreign language teachers present the minority compared to already mentioned teacher training programmes (21). English language teaching methodology as a field of potential improvement is perceived in only 9 programmes. Unfortunately, programmes through which English language teachers can build upon their knowledge of language systems and skills (phonology, grammar, lexis, discourse, speaking, listening, writing, reading) do not exist within the scope of the analysed Catalogue.